The Effect of Green Accounting and Corporate Social Responsibility on Profitability - Putri, Erlia Intan Rismaliana; Fauziah, Fitri Ella (Jurnal Rekognisi Akuntansi, 2024)
This study aims to understand how Green Accounting and Corporate Social Responsibility (CSR) affect the level of profitability of companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. This research adopts quantitative methods to produce data that can be measured accurately. Sampling was carried out using purposive sampling technique, where companies were selected based on a number of specific criteria. From this process, 19 relevant companies were obtained within three years, resulting in a total of 57 data samples. The data processing was done with the help of Microsoft Excel and SPSS software version 26. To analyze the data, methods such as descriptive analysis, classical assumption test, regression analysis, and hypothesis testing were used. The results showed that the implementation of Green Accounting and CSR has a significant positive impact on company profitability. This underscores the importance of integrating green accounting and social responsibility practices into a company's strategic planning to improve its financial performance